Versenyképesség jóléti rendszer és közjavak révén (Szociológiai Szemle, 2024)
Following the political, economic and social transformation in Hungary, the socially most sensitive problems of the cost of wages and welfare provision raise the issue of the safeguarding and financing of social provision, the changes o f the level of state support and services, the modification of the social functions of places of work and the welfare role of economic organisations. The research presented in the paper has mapped the views o f the top managers of competitive big enterprises in relation to such different developments of welfare provision like the reforms of social and health care, education and vocational training, the insurance of the unemployed, allocations to families and work-related perquisites. The experiences presented show that the management o f the competitive segment of the economy attributes great significance to the quality of human resources, therefore they consider it important in several fields - such as health care, vocational training, or housing - to increase public expenditure. From the angle of economic actors it is the welfare system offering those public goods which are the resources as well as cost of their competitiveness and by the results of which, leading to innovation, creativity, responsibility, they are able to face global competition.